The Effect of Iodine-based Contrast Material on Radiation Dose at CT: It’s Complicated - Boone, John M. (Radiology, 2017)
The studies by Sahbaee et al were well performed, and the results are provocative, but the authors of this editorial suggest that there are limitations to all modeling studies and that the results should be considered as only the first chapter in a much longer story about the role of contrast agents on radiation dose at CT.